1970
DOI: 10.1007/bf00200423
|View full text |Cite
|
Sign up to set email alerts
|

Determination and identification of sympathomimetic amines in blood samples from drivers by a combination of gas chromatography and mass spectrometry

Abstract: Summary. Gas chromatographic and mass spectrometric data concerning the analysis for certain sympathomimetie amines in blood samples from drivers are presented. In all cases where gas chromatography gave peaks at the correct retention times for amphetamine or phenmetrazine respectively, mass spectrometry confirmed the presence of the corresponding drugs in the extracts from blood. Drug-free blood samples gave neither gas chromatographic nor mass spectrometric responses at the retention times characteristic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…When only blood is available, identification can still be achieved by means of mass spectrometric methods (Bonnichsen et al, 1970a). The drug concentrations in the blood, however, are often so low that thin-layer chromatography methods are not sensitive enough.…”
Section: Methodsmentioning
confidence: 99%
“…When only blood is available, identification can still be achieved by means of mass spectrometric methods (Bonnichsen et al, 1970a). The drug concentrations in the blood, however, are often so low that thin-layer chromatography methods are not sensitive enough.…”
Section: Methodsmentioning
confidence: 99%
“…So far, Sweden is the only country to include scheduled prescription drugs (e.g., benzodiazepines) in their zero-limit legislation. However, statistics show that most DUID arrestees with a benzodiazepine in their blood also have an illicit drug present, such as amphetamine, morphine (from heroin) or THC 1, 13 We have demonstrated that the concentration of amphetamine in a single urine void was highly variable even after allowing for the prevailing blood-amphetamine concentration, the relative dilution and the pH of the specimen. Urinary pH was more important than dilution in this respect and we showed that the concentration of amphetamine decreased on average by 102 mg/L for each unit increase in pH of the urine.…”
Section: Correlation-regression Analysismentioning
confidence: 81%
“…The advent of Curie-point pyrolysers ( 12), however, has made possible the rapid and reproducible thermal decomposition of polymeric materials. A small quantity of paint (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) ng) is attached to a ferromagnetic wire which is inserted in a small induction furnace. Induction heating raises the temperature of the wire to its Curie point in a few microseconds, and the pyrolysis products are swept by carrier gas into a gas chromatograph.…”
Section: Pyrolysis Gcmentioning
confidence: 99%
“…The importance of GC and mass spectrometry in the identification of drugs and poisons is beyond dispute, as shown by the large number of papers published on this topic (15)(16)(17)(18). New sources of ions for mass spectrometry (viz., chemical ionization, field ionization, and field-desorption ionization) are significant, not only for simplifying the spectra but also in extending the range of mass spectrometry to difficult volatile materi- Identify GC Fractions at the Push of a Button identification of GC fractions.…”
Section: Chromatographic Applicationsmentioning
confidence: 99%